Establishment of the Carrot-Made LTB-Syn Antigen Cell Line in Shake Flask and Airlift Bioreactor Cultures - Carreño-Campos, Christian; Arevalo-Villalobos, Jaime I.; Villarreal, María Luisa; Ortiz-Caltempa, Anabel; Rosales-Mendoza, Sergio (Planta Medica, 2021)
Carrot (Daucus carota) cells have been used to effectively manufacture recombinant biopharmaceuticals such as cytokines, vaccines, and antibodies. We generated the carrot cell line Z4, genetically modified to produce the LTB-Syn antigen, which is a fusion protein proposed for immunotherapy against synucleinopathies. In this work, the Z4 cell suspension line was cultivated to produce the LTB-Syn protein in a 250 mL shake flask and 2 L airlift bioreactor cultures grown for 45 and 30 days, respectively. Maximum biomass was obtained on day 15 in both the airlift bioreactor (35.00 ± 0.04 g/L DW) and shake flasks (17.00 ± 0.04 g/L DW). In the bioreactor, the highest LTB-Syn protein yield (1.52 ± 0.03 µg/g FW) was obtained on day 15; while the same occurred on day 18 for shake flasks (0.92 ± 0.02 µg/g FW). LTB-Syn protein levels were analyzed by GM1-ELISA and western blot. PCR analysis confirmed the presence of the transgene in the Z4 line. The obtained data demonstrate that the carrot Z4 cell suspension line grown in airlift bioreactors shows promise for a scale-up cultivation producing an oral LTB-Syn antigen.
Keywords: Daucus carota; Apiaceae; LTB-Syn antigen; airlift bioreactor; suspension culture; synucleinopathies